2013
DOI: 10.1038/ncomms2765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing far-field thermal emission with thermal extraction

Abstract: The control of thermal radiation is of great current importance for applications such as energy conversions and radiative cooling. Here we show theoretically that the thermal emission of a finite-size blackbody emitter can be enhanced in a thermal extraction scheme, where one places the emitter in optical contact with an extraction device consisting of a transparent object, as long as both the emitter and the extraction device have an internal density of state higher than vacuum, and the extraction device has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 33 publications
(35 reference statements)
1
71
0
Order By: Relevance
“…The power emitted by a finite-size body with area A can be increased up to n 2 AσT 4 by placing the emitter in a medium of refractive index n. This is in full agreement with standard radiometry, as the radiance in a medium with refractive index n is given by n 2 I b ðT; ωÞ. This feature can be used to extract more energy from a finite-size body by using a solid immersion lens type of geometry as discussed in Refs, [56,57].…”
Section: Discussionmentioning
confidence: 58%
“…The power emitted by a finite-size body with area A can be increased up to n 2 AσT 4 by placing the emitter in a medium of refractive index n. This is in full agreement with standard radiometry, as the radiance in a medium with refractive index n is given by n 2 I b ðT; ωÞ. This feature can be used to extract more energy from a finite-size body by using a solid immersion lens type of geometry as discussed in Refs, [56,57].…”
Section: Discussionmentioning
confidence: 58%
“…Due to the spectrally tunable slow-light principle, the effective refractive index of the super absorptive hyperbolic metafilm pattern is very large, particularly for mid-far IR wavelengths, which is not naturally available. Therefore, being able to create a high index super absorptive/emissive material for mid-far IR wavelengths will provide a technological foundation for a variety of thermal applications, including extraction of more thermal energy from a more compact thermal emitter49, miniaturizing the dimension and improving the performance of conventional heat-to-light converters, thermophotovoltaic cells and radiative coolers/heaters50. This absorption engineering will lead to the development of controllable, effective media, and improve our ability to manipulate light in man-made metasurfaces that do not exist in the natural world51.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a number of works have demonstrated that near-field radiative heat transfer is enhanced by many orders of magnitude compared to the far-field limit for closely spaced objects with either natural 10,11 or engineered resonant surface modes [12][13][14][15][16] . There have also been efforts to couple these near-field modes into the far-field with the use of grating structures 17 , antennas 18 , and a thermal extraction lens 19,20 .…”
mentioning
confidence: 99%